STRUCTURAL CHANGES OF THE VASCULAR BED OF THE RAT BRAIN CORTEX IN THE BODY UNDER THE ACTION OF COPPER SULFATE, ZINC AND IRON - Romaniuk, A.M.; Grintsova, N.; Romaniuk, S.; Kozik, E. (World of Medicine and Biology, 2014)
In the experiment, 48 adult male rats aged 5-8 months who are within 3 months of consumed water saturated with a combination of heavy metal salts of zinc, copper and iron, the mixture of heavy metals has on blood vessels of the cerebral cortex is quite expressive vazotoksichny effect. The degree of severity of morphological transformations in the bloodstream is directly dependent on the timing of the experiment. In the early stages of experience observed functional disorders of hemodynamics (dystonic vascular changes, blood stasis). With the increase in terms of restructuring the experiment take signs of organic polymorphic (increased permeability of the vessel walls, perivascular edema formation, sludge phenomenon, education diapedetic hemorrhage into the brain tissue, hemorrhagic infiltration of the brain tissue).